The tendencies of the development of mathematics methodics in 5–6th grades of basic school on the aspect of interpretative pedagogy - Cibulskaitė, Nijolė (Lietuvos matematikos rinkinys, 2011)
By studying education methodology applied by teachers of mathematics it was researched how often mathematics teachers apply modern learning and teaching activities in 5–6th grades of basic school. The results of several researches performed in 2004–2010 are presented in this article and summarized in this aspect. The research results let draw the conclusions: mathematics teachers more frequently applied such traditional methods as independent work and self-control, the work with visual manuals; mathematics teachers must pay more attention to the control in pairs, work in groups, choose of the work’s variant, emphasize of historical elements, organization of mathematics excursions; the frequency of student’s work with computer in the classroom and at home and the project’s making is increasing now.